Comparison of flares in 85 patients with SLE who maintained, discontinued or reduced dose of hydroxychloroquine during a prospective study of ophthalmological screening for retinopathy (PERFOCTAPS Study) - Nathalie Costedoat-Chalumeau; Alexis Mathian; Luc Mouthon; Yann Nguyen; Kevin Chevalier; Veronique Le Guern; Nathalie Morel; Vivien Vasseur; Joana Isabel Marques Dias; Elsa Laumonier; Sabine Derrien; Martine Mauget Faÿsse (Lupus Science and Medicine)
Objective Little is known about the risk of SLE flares associated with hydroxychloroquine (HCQ) reduction or cessation, especially after ophthalmological screening. We analysed the risk of SLE flares after HCQ reduction or discontinuation after detection of early ophthalmological toxicity.Methods This study includes all patients with SLE among the 109 included in the prospective PERFOCTAPS Study and treated with HCQ for at least 5 years. Patients were divided into 3 groups: HCQ maintenance, reduction and discontinuation after intensive ophthalmological screening. Flare occurrence (SELENA-SLEDAI Flare Index) was assessed for 2 years after HCQ reduction or discontinuation or after inclusion in the maintenance group.Results This study included 85 patients (98% women, mean age 40.0 years, and mean durations of SLE and HCQ treatment 14.4±7.7 years and 12.9±7.2 years, respectively). The PERFOCTAPS Study identified ophthalmological abnormalities in 25 patients (29.4%); these led to dose reduction in 20 patients and discontinuation in 5. Flares occurred in 29 patients (34.1%): 17 (28.3%) in the maintenance group, 10 (50%) in the reduction group and 2 (40%) in the discontinuation group. After adjustment for potential confounders, HCQ reduction was independently associated with the risk of flare (adjusted HR 2.26; 95% CI 1.03 to 4.97). The same trend was observed in the discontinuation group, but was no longer statistically significant (adjusted HR 2.13; 95% CI 0.44 to 10.27).Conclusion In this prospective study, HCQ reduction due to early suspicion of retinal toxicity was associated with a statistically significantly increased risk of disease flare.Trial registration number NCT02719002.